The legal framework for commercial and investment activity in Libya - Farhat Muhammad Farhat; Farhat Muhammad Farhat (Journal of Libyan Academy Bani Walid, 2021)
The category of persons with disabilities is considered one of due to the physical or mental challenges they face. Although human rights apply to them, attention to these rights was not prominent on the international stage when the United Nations was working on drafting international charters. Due to the shortcomings of the mechanisms available to ensure the protection of their rights, there was an urgent need to create an international treaty that addresses their rights in line with their specific needs. In this context, after arduous efforts, the United Nations issued the "Convention on the Rights of persons with Disabilities" in 2006, which covered all civil, political, economic, social, and cultural rights. The purpose of this convention is to ensure comprehensive protection of the rights of persons with disabilities, ensuring full equality and non_discrimination based on disability, thereby enhancing their opportunities for participation and integration into society.